Distant suffering : morality, media, and politics - Boltanski, Luc (Cambridge cultural social studies., 1999)
What is the morally acceptable response to images of starving children, bombed villages and mass graves brought to us by television? Luc Boltanski discusses the ways in which spectators have tried to respond to what they have seen and asks if there remains a place for pity in modern politics.